XACML-based semantic rules language and ontological model for reconciling semantic differences of access control rules. (12th May 2023) - Manal, Lamri; Lyazid, Sabri
Internet of things interconnects increasing numbers of artefacts and individuals, allowing the setup of ambient intelligence systems in multi-domains (e.g., hospitals). Designing a suitable architectural framework is required to ensure the efficiency and sustainability of the implementation of such systems. Consolidating public services about citizens' safety and authorisation decisions when a resource is accessed in an open-dynamic environment are the main challenges that can be highlighted. Therefore, the semantic heterogeneity between the local policies of the different domains is a crucial lock for implementing this process. Our approach goes beyond the semantic web languages' weaknesses by combining the XACML-based security policy model with a semantic rules language developed during the European SembySem Project. Built on top of RDF(S), the proposed model aims to abstract the security implementation, reconcile semantic differences across multi-domain, and maintain the local security policy. Moreover, this model addresses the semantic heterogeneity of sensors' data during knowledge-sharing.